2018
DOI: 10.1007/s11999.0000000000000060
|View full text |Cite
|
Sign up to set email alerts
|

Is Treatment With Dithiothreitol More Effective Than Sonication for the Diagnosis of Prosthetic Joint Infection?

Abstract: In this randomized study, we found no difference in sensitivity between DTT and sonication for the detection of PJI, and both of those tests were more sensitive than standard tissue cultures. Thus, cultures of sonication or DTT fluid should be considered important additional tools to standard cultures for definition of PJI and should be considered together with other criteria, especially in settings where infection is not suspected before revision surgery.Level of Evidence Level I, diagnostic study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 19 publications
1
35
0
Order By: Relevance
“…ical culture media and it was shown that DTT cultures have a superior sensitivity than cultures from sonication fluid (85.7 vs. 71.4 %) with the same specificity (94.1 %). Another study with 232 patients by Sambri et al showed the same results with a sensitivity [24] of 91 % and a specificity of 99 % for the DTT cultures [32].…”
Section: Discussionmentioning
confidence: 58%
“…ical culture media and it was shown that DTT cultures have a superior sensitivity than cultures from sonication fluid (85.7 vs. 71.4 %) with the same specificity (94.1 %). Another study with 232 patients by Sambri et al showed the same results with a sensitivity [24] of 91 % and a specificity of 99 % for the DTT cultures [32].…”
Section: Discussionmentioning
confidence: 58%
“…As DTT is often one of cell culture media components and can be added directly to the medium [75], studies have demonstrated that DTT lacks selectivity and spatial resolution [76] and leads to cellulose-anchored biofilm formation in Mycobacterium tuberculosis cultures, which contain metabolically active but drug-tolerant bacteria [77,78]. Importantly, in certain studies, while DTT has been implemented as a therapy-oriented approach or treatment of some syndromes and complications [63,79], its efficacy remains poorly understood [80]. Therefore, we think it is necessary to summarize the current studies to highlight the potential risks of DTT-involved approaches as presented graphically in Figure 3.…”
Section: Current Insights Into the Dtt-induced Reductive Stressmentioning
confidence: 99%
“…Moreover, the concentration of DTT is closely related to DNA protection or DNA damage [74]. In addition, further investigations on its drug-tolerance and therapy as well as efficacy should also be highly warranted [63,[77][78][79][80]. 4 Oxidative Medicine and Cellular Longevity morphological abnormalities cannot be identified in some studies in spite of the presence of severe cardiomyopathy and mitochondrial dysfunction [88].…”
Section: Downregulationmentioning
confidence: 99%
“…Adjunctive techniques to improve the identification of an infecting organism should be considered even though not used in this case report. To potentially reduce false negative culture results, a study by Sambri et al reported that the culture of fluid from explanted components treated with either sonication or dithiothreitol improved sensitivity compared to routine tissue culture [12]. Alternatively, Zannoli et al and Sambri et al demonstrated that polymerase chain reaction (PCR) assays could also be used to assist in the timely identification of organisms [13,14].…”
Section: Case Reports In Orthopedicsmentioning
confidence: 99%